Associations between the Transsexual Voice Questionnaire (TVQMtF) and self‐report of voice femininity and acoustic voice measures. Issue 6 (19th April 2017) - Dacakis, Georgia; Oates, Jennifer; Douglas, Jacinta
Abstract: Background: The Transsexual Voice Questionnaire (TVQ MtF ) was designed to capture the voice‐related perceptions of individuals whose gender identity as female is the opposite of their birth‐assigned gender (MtF women). Evaluation of the psychometric properties of the TVQ MtF is ongoing. Aims: To investigate associations between TVQ MtF scores and (1) self‐perceptions of voice femininity and (2) acoustic parameters of voice pitch and voice quality in order to evaluate further the validity of the TVQ MtF . A strong correlation between TVQ MtF scores and self‐ratings of voice femininity was predicted, but no association between TVQ MtF scores and acoustic measures of voice pitch and quality was proposed. Methods & Procedures: Participants were 148 MtF women (mean age 48.14 years) recruited from the La Trobe Communication Clinic and the clinics of three doctors specializing in transgender health. All participants completed the TVQ MtF and 34 of these participants also provided a voice sample for acoustic analysis. Pearson product‐moment correlation analysis was conducted to examine the associations between TVQ MtF scores and (1) self‐perceptions of voice femininity and (2) acoustic measures of F0, jitter (%), shimmer (dB) and harmonic‐to‐noise ratio (HNR). Outcomes & Results: Strong negative correlations between the participants' perceptions of their voice femininity and the TVQ MtF scores demonstrated that for this group of MtF women a low self‐rating of voice femininity was associated with more frequent negative voice‐related experiences. This association was strongest with the vocal‐functioning component of the TVQ MtF . These strong correlations and high levels of shared variance between the TVQ MtF and a measure of a related construct provides evidence for the convergent validity of the TVQ MtF . The absence of significant correlations between the TVQ MtF and the acoustic data is consistent with the equivocal findings of earlier research. This finding indicates that these two measures assess different aspects of the voice‐related experience. Conclusions & Implications: Evidence supporting the validity of the TVQ MtF is strong and indicates that it is a sound measure for capturing the MtF woman's self‐perceptions of her vocal functioning and how her voice impacts on her everyday life.